2016
DOI: 10.1016/j.bbrc.2016.04.149
|View full text |Cite
|
Sign up to set email alerts
|

A bitter pill for type 2 diabetes? The activation of bitter taste receptor TAS2R38 can stimulate GLP-1 release from enteroendocrine L-cells

Abstract: The bitter taste receptor TAS2R38 is a G protein coupled receptor (GPCR) that has been found in many extra-oral locations like the gastrointestinal (GI) system, respiratory system, and brain, though its function at these locations is only beginning to be understood. To probe the receptor’s potential metabolic role, immunohistochemistry of human ileum tissues was performed, which showed that the receptor was co-localized with glucagon-like peptide 1 (GLP-1) in L-cells. In a previous study, we had modeled the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 39 publications
0
39
0
3
Order By: Relevance
“…Consistent with the role of BTR signaling in GLP-1 secretion, the effect of DB to slow gastric emptying was abolished by co-administration of probenecid ( 26 ). Similarly, intragastric administration of PTC has been reported to augment plasma GLP-1 concentrations ( 36 ) and slow gastric emptying ( 26 ) in mice. The latter effect was, however, not inhibited by probenecid ( 26 ).…”
Section: Effects Of Btr Signaling On Gut Hormone Secretionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with the role of BTR signaling in GLP-1 secretion, the effect of DB to slow gastric emptying was abolished by co-administration of probenecid ( 26 ). Similarly, intragastric administration of PTC has been reported to augment plasma GLP-1 concentrations ( 36 ) and slow gastric emptying ( 26 ) in mice. The latter effect was, however, not inhibited by probenecid ( 26 ).…”
Section: Effects Of Btr Signaling On Gut Hormone Secretionmentioning
confidence: 99%
“…Consistent with PCR observation, studies using double-labeling immunofluorescence have also shown co-localization of chromogranin A (a cellular marker of enteroendocrine cells) with T2Rs in the mouse small and large intestine ( 42 , 44 ). More specifically, co-expression of GLP-1 with various T2Rs in human enteroendocrine L cell lines (i.e., HuTu-80 and NCI-h716) and in small and large intestinal tissues has been observed ( 21 , 35 , 36 , 39 ). However, the co-expression of T2Rs with enteroendocrine cells containing other hormones is not well characterized in rodents or humans.…”
Section: Intestinal Bitter Taste Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…STC-1 is originated from mouse duodenal tumours, while HuTu-80 is originated from a human duodenal adenocarcinoma. Both STC-1 and HuTu-80 cells are able to secrete GLP-1 upon nutrient stimulation, and are often used as cell models for studying GLP-1 secretion (Geraedts et al, 2011;Pham et al, 2016). However, GLP-1 secretion is not always similar among species (Kuhre et al, 2014) and cell lines (Kuhre et al, 2016).…”
Section: Introductionmentioning
confidence: 99%